Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$ \sum^{n}_{j=1}\sum^{n}_{k=1} jk $$ How do I simplify this? Also can someone explain how this works? its gonna be like this right? or am I misunderstanding it? $$ \sum^{n}_{j=1}(j+2j+3j+...+nj) $$

share|cite|improve this question
Just note that $$\sum_{j=1}^{n}\sum_{k=1}^{n}jk = \left(\sum_{j=1}^{n} j\right)\left(\sum_{k=1}^{n} k\right) = \left(\sum_{j=1}^{n} j\right)^2.$$ – Sangchul Lee Nov 13 '12 at 10:26
huh? why did it become summation of j squared? when j and k are not equal? – Maximus Programus Nov 13 '12 at 10:30
up vote 5 down vote accepted

Yes, the nested summation reads $\sum^{n}_{j=1}\bigl(\sum^{n}_{k=1} jk\bigr)$. In this case you can see that all terms in the inner summation have a factor $j$ that does not depend on the summation index ($k$) in common, so you can factor that out: $\sum^{n}_{j=1}\bigl(\sum^{n}_{k=1} jk\bigr)=\sum^{n}_{j=1}\bigl(j\sum^{n}_{k=1} k\bigr)$. Now the inner summation itself does not depend on the index ($j$) of the outer summation, so it can be factored out of that, and becomes a separate summation: $\sum^{n}_{j=1}\bigl(j\sum^{n}_{k=1} k\bigr)=\bigl(\sum^{n}_{k=1} k\bigr)\bigl(\sum^{n}_{j=1}j\bigr)$. Now you can do both summations, which are not nested, separately (I trust you know how to do this); in fact they are the same summation, with a different name for the summation variable. All in all you get the square of the value of $\sum^{n}_{i=1} i$.

You won't of course always be as lucky when doing nested summations; often there is simply no simpler way to write them.

share|cite|improve this answer

$j$ is constant over the inner sum, so move it out of the sum:

$\sum_{j=1}^{n} \sum_{k=1}^n jk = \sum_{j=1}^{n} \left( j \sum_{k=1}^n k\right)$

Now the whole inner sum is constant for the outer sum, move it out:

$\sum_{j=1}^{n} \left(j \sum_{k=1}^n k\right) = \left( \sum_{k=1}^n k \right) \left( \sum_{j=1}^n j \right) $

Now both sums are easy to evaluate:

$\left( \sum_{k=1}^n k \right) \left( \sum_{j=1}^n j \right) = \left( \frac{n(n+1)}{2} \right)\left( \frac{n(n+1)}{2} \right) = \left( \frac{n(n+1)}{2} \right)^2$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.